Skill Training for Swallowing Rehabilitation in Patients With Parkinson's Disease - Athukorala, Ruvini P.; Jones, Richard D.; Sella, Oshrat; Huckabee, Maggie-Lee (Archives of physical medicine and rehabilitation, 2014)
To examine the effects of skill training on swallowing in individuals with dysphagia secondary to Parkinson's disease (PD) and to explore skill retention after treatment termination. Within-subject pilot study with follow-up after 2 weeks of treatment and after a 2-week nontreatment period. Clinic in a research institute. Patients (N=10; mean age, 67.4y) included 3 women (mean Hoehn and Yahr score, 2.6) and 7 men (mean Hoehn and Yahr score, 2.4). Patients underwent 10 daily sessions of skill training therapy focused on increasing precision in muscle contraction during swallowing using visual feedback. Data from the timed water swallow test, Test of Mastication and Swallowing Solids, surface electromyography (sEMG) of submental muscles, and swallowing-related quality of life questionnaire were collected at 2 baseline sessions (conducted 2wk apart) at the end of treatment and after 2 nontreatment weeks to assess skill retention. Immediately after posttreatment, the swallowing rate for liquids (P=.034), sEMG durational parameters of premotor time (P=.003), and preswallow time (P<.001) improved. A functional carryover effect was seen from dry to water swallows (P=.009). Additionally, swallowing-related quality of life improved (P=.018). Reassessment at 2 weeks after treatment termination revealed short-term retention of treatment effects. A skill-based training approach produced functional, biomechanical, and swallowing-related quality of life improvements in this cohort indicating compelling evidence for the effectiveness of this novel approach for dysphagia rehabilitation in PD.